1993
DOI: 10.1037/0022-3514.64.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Eysenck's arousal theory of introversion€xtraversion: A converging measures investigation.

Abstract: Convergent electroencephalographic, performance, and psychometric measures of arousal were used to test predictions based on H. J. Eysenck's (1967) theory. Twelve introverts and 12 extraverts had their brainstem auditory evoked responses (BAERs) monitored under 3 levels of caffeine administration (0.0, 1.5, and 3.0 mg/kg) and 3 levels of task demand (resting, simple response time, and complex response time). Results revealed a decrease in the latency of Wave V of the BAER as a function of personality, with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 78 publications
1
24
0
2
Order By: Relevance
“…Studies have shown faster brainstem transmission is associated with adult introversion (Andress and Church, 1981). The faster brainstem transmission in introverted personalities could be a reflection of increased arousal in the ascending reticular activating system that is, higher levels of brainstem arousal (Bullock and Gilliand, 1993;Matthews and Gilliland, 1999;Swickert and Gilliand, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown faster brainstem transmission is associated with adult introversion (Andress and Church, 1981). The faster brainstem transmission in introverted personalities could be a reflection of increased arousal in the ascending reticular activating system that is, higher levels of brainstem arousal (Bullock and Gilliand, 1993;Matthews and Gilliland, 1999;Swickert and Gilliand, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Brocke et al (1997) found that introverts had smaller P300 amplitudes than extraverts under conditions of supraoptimal arousal, indicating that introverts invest more effort under these conditions. This result was of special importance, because the concept of the control system was initially introduced by Eysenck (1982) to explain why supraoptimal arousal levels were not found to impair the performance of introverts (Bakan, 1959;Bullock and Gilliland, 1993;Davies and Hockey, 1966;Keister and McLaughlin, 1972). Therefore, the P300 amplitude was also expected to function as an effort indicator for introverts in supraoptimal arousal conditions.…”
Section: Introductionmentioning
confidence: 87%
“…Many studies failed to confirm this prediction (Bakan, 1959;Bullock and Gilliland, 1993;Davies and Hockey, 1966;Keister and McLaughlin, 1972). Eysenck (1982Eysenck ( , 1988 and Hockey (1986Hockey ( , 1988 explained the failure to reduce the performance of introverts through sensory stimulation (e.g.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The efficacy of certain training interventions has been demonstrated to interact with individual and environmental factors, which greatly complicates the process of determining which training methods are likely to be most effective for different people in different settings. For example, although it is known that performance generally follows an inverted U shape with level of arousal (i.e., performance deteriorates when a person is under-or overexcited), there is evidence that personality differences such as introversion and extroversion result in different baselines of arousal, and, consequently, the same stimulus effect may increase performance for an extrovert while decreasing performance for an introvert [Revelle et al 1980;Bullock and Gilliland 1993]. Revelle et al's study also showed interactions between several other factors, including time of day, other personality factors, and consumption of stimulants.…”
Section: Other Human Phenomena Influencing Skill Acquisitionmentioning
confidence: 97%